(untitled) (Journal of Mathematics Mechanics and Computer Science, 2012)
We carried out a study of technology development of the parallel algorithm for computing the 3-D heat equation using mpiJava technologies, as well as the organization of parallel computations with different levels of decomposition. The obtained approximate solution is compared with the analytical solution, while achieving sufficient accuracy of solutions.